2019
DOI: 10.1002/smll.201900860
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Silver Nanoparticles and Two Dehydrogenases: Role of Thiol Groups

Abstract: Widely used silver nanoparticles (AgNPs) are readily accessible to biological fluids and then surrounded by proteins. However, interactions between AgNPs and proteins are poorly understood. Two dehydrogenases, glyceraldehyde‐3‐phosphate dehydrogenase (GAPDH) and malate dehydrogenase (MDH), are chosen to investigate these interactions. Ag bound to thiol groups of these enzymes significantly decreases the number of free thiols available. Dose‐dependent inhibition of enzyme activities is observed in both AgNPs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 69 publications
0
51
0
1
Order By: Relevance
“…Bio‐AgNPs from E. citriodora leaf extract inhibited biofilms in C. albicans due to the alteration of membrane surface charges of pathogenic fungi following the exposure to the nanoparticles, leading to membrane disruption (Paosen et al, 2019). The release of Ag + from AgNPs was demonstrated to react with the thiol group of protein portion, generally presented in microbial enzymes, such as glyceraldehyde‐3‐phosphate dehydrogenase and malate dehydrogenase, resulting in pathogen inactivation (Jiang et al, 2019). Other workers demonstrated that AgNPs synthesized using S. cumini seed extract reduced Candida biofilm because the nanoparticles could anchor onto the cell surface and penetrate into the cytoplasm causing morphological damages (Jalal et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Bio‐AgNPs from E. citriodora leaf extract inhibited biofilms in C. albicans due to the alteration of membrane surface charges of pathogenic fungi following the exposure to the nanoparticles, leading to membrane disruption (Paosen et al, 2019). The release of Ag + from AgNPs was demonstrated to react with the thiol group of protein portion, generally presented in microbial enzymes, such as glyceraldehyde‐3‐phosphate dehydrogenase and malate dehydrogenase, resulting in pathogen inactivation (Jiang et al, 2019). Other workers demonstrated that AgNPs synthesized using S. cumini seed extract reduced Candida biofilm because the nanoparticles could anchor onto the cell surface and penetrate into the cytoplasm causing morphological damages (Jalal et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…However, a preliminary surface modification of the nanoparticle with thiol group source serving molecules such as 1,2-dioleoyl-sn-glycero-3-phosphoethanolamine-N- [ Other AgNP stabilizing and capping moieties that afford a thiol functionality to the AgNPs for their further bio-conjugation include alkylthiols: HS(CH2)nCH3 (n=11); thioalkyl acids: HS(CH2)nCH3 (n = 10); thioalkyl amines: HS(CH2)nNH2 (n=2); and thioalkyl-PEG-R (R = H, CH3, CH2COOH, NH2) [87]. Besides, the strong covalent/ dative linkages and surface adsorption, thiol group also interacts directly with the AgNPs surface through considerable electrostatic interactions between the sulfur atom and the nanoparticle [88]. Furthermore, the thiol-containing biomolecules such as cysteine, cysteamine, homocysteine, glutathione that interact with the nanoparticle surface by non-covalent electrostatic interactions through their 'S' atom under acidic conditions assist in the colloidal stabilization of AgNPs and essentially, serve as linker molecules for tethering AgNPs to the biomolecule of interest [89,90].…”
Section: Thiol/ Sulfide Anchoring Of Agnps For Conjugation With Biomomentioning
confidence: 99%
“…A robust freestanding film (FSF) was easily manufactured from the PSSLGS solution by vacuum filtration because of the molecular‐level contacts (e.g., disulfide–silver, graphene–silver, and π–π interactions) (Figure 1). [ 23,24 ] After filtration, the PSSLGS residue formed on the nylon filter coagulated upon immersion in acetone. The resulting PSSLGS FSF was highly flexible and easily folded and unfolded (Figure S14a, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, mixing AgNWs with graphene may reduce their contact resistance as graphene acts as a heat spreader to prevent the breakage of AgNWs at high temperatures. However, because AgNWs and graphene tend to significantly aggregate owing to mutual interactions, [ 22–27 ] the poor dispersion of AgNWs and graphene may prevent heat dissipation and may lead to AgNW breakage during Joule heating. Therefore, molecular‐level contact between AgNWs and graphene is required to stabilize the conducting hybrid network system.…”
Section: Introductionmentioning
confidence: 99%